University students’ perception of using ChatGPT toward their writing skills - Annisa Melfida Chairiah; Warno Edi; Dewi Yana (Celtic : A Journal of Culture, English Language Teaching, Literature and Linguistics, 2025)
This study investigated students' perceptions of the use ofChatGPT on their writing skills in the context of learning Englishas a Foreign Language (EFL). Using a descriptive qualitativedesign supported by quantitative data, 53 students from theDepartment of English Language Education at the University ofRiau Islands participated in a questionnaire and semi-structuredinterviews. The study findings indicated that students' overallperception of ChatGPT was moderate (M = 3.57). The highestmean was found for Perceived Ease of Use (3.75), and thelowest for Output Quality (3.47). Students with highperceptions described ChatGPT as an effective, user-friendly,and motivating writing assistant that enhanced theirproductivity, creativity, and confidence in composing academictexts. In contrast, students with low perceptions tended to becautious, emphasizing the importance of originality, criticalthinking, and ethical use. Significantly, the study's findingsvalidate the application of the Technology acceptability Model(TAM), namely that students' who perceived ChatGPT as easyto use were more likely to use and integrate it into their writingprocess, while concerns about accuracy reduced acceptanceamong students with low perceptions. This study concludesthat while ChatGPT can be a useful tool for improving EFLstudents' writing skills, its implementation must be governed bya pedagogical framework that fosters ethical awareness andresponsible AI literacy. These results offer pedagogicalimplications for EFL teachers and curriculum designers increating writing instruction that intentionally and morallyincorporates AI tools in higher education contexts, as well asproviding theoretical reinforcement for TAM.